Wintering geese of northwestern Black Sea coasts: results of coordinated monitoring 2017–2022 - Iliev, Mihail; Todorov, Emil; Russev, Ivan; Popgeorgiev, Georgi; Fox, Anthony D.; Petkov, Nicky (Wildfowl, 2023)
Northwestern Black Sea coasts support globally important numbers of wintering geese, especially Red-breasted Geese (RBG) Branta ruficollis but also large numbers of Greater White-fronted Geese (GWFG) Anser albifrons and regionally important Greylag Geese (GG) Anser anser. Despite good national mid-winter waterbird counts within Bulgaria, Romania and Ukraine, until recently there were no internationally coordinated counts at other times of the winter. Here, we present coordinated monthly count data from November to February in five recent winters (2017/18–2021/22) from the three countries, collected under a LIFE programme project to support RBG conservation. Mean annual maximum winter counts were 385,363 GWFG (range = 207,655–530,100), 20,919 RBG (13,741–26,834) and 9,728 GG (4,059–13,971) from standardised counts at the same sites throughout the region. Romania supported an overall mean of 77.3% of all GWFG from any one total count in all winter months, 65–95% in all years except for the mild winter of 2018/2019. Romania also contributed 66.3% of all RBG (range = 27%–92%) counted during coordinated international counts. Peak numbers of GWFG tended to occur in Romania in December, but corresponding increases in Bulgaria in January 2019 were the only suggestion of within-winter westward movements. Peak numbers of RBG in all winters generally were counted from January onwards, but again there were no clear patterns of consistent between-country movements in the course of the winter. These data provide a vital baseline for assessing the effects of recent warfare in the region on the distribution and abundance of these critical goose populations, and underline the need for long-term coordinated monitoring over as large an area and as many wetlands as possible in future, in order to understand their long-term trends and the factors affecting them. Such data are also essential to support planning of effective conservation measures and better inform planning issues, such as those posed by wind turbine development occurring throughout the region.